Pengaruh Infrastruktur terhadap Kemiskinan dengan Menggunakan Data Panel 34 Provinsi di Indonesia - Fery Andrianus; Khaira Alfatih (SAFE-Network, 2023)
This study aims to analyze how the influence of infrastructure consisting of sanitation, electricity and roads on poverty levels in Indonesia, either simultaneously or partially. This study uses a quantitative method in the form of multiple regression analysis with panel data. The type of data used is secondary data from 34 provinces in Indonesia during the 2015-2019 period obtained from the Central Statistics Agency which includes: data on the percentage of the number of poor people, data on the length of roads and the area of the province, data on the percentage of households that have access to PLN electricity, and data on the percentage of households that have access to proper sanitation services. The results of the analysis using a random effect model approach show that sanitation, electricity and road infrastructure have a significant negative effect on poverty levels. This means that an increase in each infrastructure has an effect on reducing the percentage of poor people in Indonesia. Thus, it is evident that the increase in each variable of sanitation, electricity and roads has a significant effect on reducing the percentage of the number of poor people in Indonesia.